Electron Delocalization Explains much of the Branching and Protobranching Stability. Issue 33 (18th July 2013) - Kemnitz, Carl R.
<x xml:space="preserve">Abstract</x> Delocalization in alkanes? The case is made for the role of electron delocalization as a cause for the greater stability of branched alkanes relative to their linear isomers. Electron delocalization plays a similar role in linear alkanes as manifest in "protobranching stabilization." A sizeable component of the stabilization is found to be attributable to geminal σ→σ* delocalization.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>